Chronic inflammation involves CCL11 and IL-13 to facilitate the development of liver cirrhosis and fibrosis in chronic hepatitis B virus infection - Wong, Sui-Weng (Taylor & Francis, 2021)
The pathogenesis involving non-alcoholic fatty liver disease (NAFLD) in the context of chronic HBV (CHB) virus infection requires to be understood for developing improved modalities of diagnosis and treatment. We retrospectively investigated the association between NAFLD and CHB virus infection in the context of liver fibrosis. Among the 522 consecutive CHB patients who underwent transient elastography between years 2013 and 2016, we studied 455 subjects in the current investigation. Controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) scores were generally higher in patients with steatosis and fibrosis or cirrhosis. Antiviral treatment had significantly reduced the hepatitis B virus (HBV) viral load. Other liver function markers showed a significant positive correlation with both CAP and LSM scores. Plasma IL-13 was independently associated with increased CAP score where every increase of 1 unit of IL-13 was associated with an increase in CAP score by 0.98 unit. CCL11 was independently associated with LSM with every increase of CCL11 by a unit that, in turn, was associated with an increase of LSM score. We found that there was a high concurrence of NAFLD among patients with CHB virus infection. The presence of metabolic syndrome and chronic inflammation in CHB virus-infected patients were two independent factors that led to the progression of liver cirrhosis, with IL-13 playing the key role in linking the metabolic with the inflammatory components.